1999
DOI: 10.1007/s002449900447
|View full text |Cite
|
Sign up to set email alerts
|

A Study for the Proper Application of Urinary Naphthols, New Biomarkers for Airborne Polycyclic Aromatic Hydrocarbons

Abstract: Urinary naphthols, 1- and 2-naphthol, recently have been suggested as route-specific biomarkers for exposure to airborne polycyclic aromatic hydrocarbons. For the proper application of urinary naphthols as biomarkers, we studied effects of lifestyle on urinary naphthols levels in 119 Japanese male workers. After improving the detection limit of urinary naphthols up to 0.27 microg/L by high-resolution capillary gas chromatography/mass spectrometry/selected ion monitoring, urinary naphthols were detectable in ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
56
2
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 19 publications
8
56
2
4
Order By: Relevance
“…Polycyclic aromatic hydrocarbons (PAHs), which are environmental carcinogens formed by the incomplete combustion of organic material, have been a major focus of research [Yang et al, 1999]. Humans may be exposed to PAHs through the air, soil, food, their occupation, and their lifestyle [Jongeneelen, 1994].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polycyclic aromatic hydrocarbons (PAHs), which are environmental carcinogens formed by the incomplete combustion of organic material, have been a major focus of research [Yang et al, 1999]. Humans may be exposed to PAHs through the air, soil, food, their occupation, and their lifestyle [Jongeneelen, 1994].…”
Section: Introductionmentioning
confidence: 99%
“…These types of studies are complicated by the varying bioavailability of PAHs from different exposure pathways (e.g., via inhalation, food consumption, skin contact), as well as individual differences in susceptibility to PAH exposure. Recently, genetic differences in the enzymes important for the metabolism of PAHs have been evaluated as susceptibility biomarkers for PAH biomonitoring [Yang et al, 1999;Nerurkar et al, 2000]. However, it is difficult to observe the effects of genetic differences on biological monitoring without considering all the major exposure routes of PAHs.…”
Section: Introductionmentioning
confidence: 99%
“…Cytochromes p-450 (CYP) is a family of biotransformation phase I enzymes which catalyze the metabolism of xenobiotics. CYP1A1 catalyzes the oxidation of PAH and the formation of their active oxygen metabolites [16][17][18] . Glutathione S-transferases (GSTs) are biotransformation phase II enzymes, which have been reported to catalyze the conjugation of PAH diol epoxide metabolites with reduced glutathione.…”
mentioning
confidence: 99%
“…Naphthalene tends to be the predominant airborne compound in the processing and handling of coal tar products 1,16) , in iron foundry 29) and in creosote impregnation plants 30,31) Naphthalene is metabolized almost exclusively to 1-naphthol and 2-naphthol 16) . Detection of naphthols in the urine is the most widely used indicator of naphthalene exposure 32,33) As seen in Table 2, concentrations of naphthol isomers are higher in the urine of workers engaged in the naphthalene oil distillation than in the tar distillation departments, but are not statistically significant. Differences between the concentrations of 1-naphthol and 2-naphthol detected in the urine of exposed and nonexposed subjects are statistically significant.…”
Section: · Grazyna Bieniek Et Al: External and Internal Exposures Tmentioning
confidence: 99%
“…Differences between the concentrations of 1-naphthol and 2-naphthol detected in the urine of exposed and nonexposed subjects are statistically significant. Earlier investigations were able to determine simultaneously the presence of 1-naphthol and 2-naphthol in the urine of workers employed at the naphthalene oil distillation process in a coke plant 32) . It was found that the concentrations of the naphthols were significantly higher than in the present results.…”
Section: · Grazyna Bieniek Et Al: External and Internal Exposures Tmentioning
confidence: 99%